The earliest belemnite linked with the Carnian Pluvial Episode - Ma, Zhiheng; Zhang, Tingshan; Chen, Jingwen; Popa, Mihai Emilian; Li, Hongjiao; Li, Shixin; Zeng, Jianli; Zhang, Xi (Frontiers in Ecology and Evolution, 2023)
Sinobelemnites from the Upper Triassic (Carnian, Julian 2) of the Luxi County, Yunnan Province, Southwest China are described and discussed, with two species: Sinobelemnites maantangensis Zhu and Bian, 1984 and Sichuanobelus luxiensis sp. nov. Sichuanobelus luxiensis sp.nov. is has a rostrum with a single alveolar groove along the dorsal side, with the rostral diameter increasing quickly along the rostrum cavum region. The rough rostral surface of Sinobelemnites is typical for the group. The occurrence of belemnites during the Carnian, especially during the Carnian Pluvial Episode (CPE), indicates the CPE as a drive for belemnite flourishment.and preservation.